Could Toxomplasma gondii infection be dangerous? - Systematic review - Gabriela Frącz; Klaudia Kuliga; Marcin Kuliga; Kinga Musz; Agnieszka Socha; Kinga Śnieżek (Journal of Education, Health and Sport, 2023)
Introduction:  Toxoplasma gondii is an intracellular protozoan commonly found in humans in the form of three main forms: tachyzoite, tissue cyst and oocyst. The definitive host is the Felidae family, and one of the intermediate hosts is humans. The most common routes of infection are ingestion of raw or undercooked meat, water and food contaminated with oocysts. Among the forms of infection, we distinguish between the acquired form and the much more dangerous congenital form.